Step towards home-based robotic rehabilitation : an interface circuit for EEG : SEMG actuated orthosis - Gunadi Wihardjo. (2009)
The world is faced with an urgent need for rehabilitation devices which fulfill clinical requirements, which are cheap, modular, versatile, compatible, easy to set up and monitored. In addition, the patient should be able to perform round-the-clock rehabilitation.